2020
DOI: 10.1037/xlm0000849
|View full text |Cite
|
Sign up to set email alerts
|

Early activation of cross-language meaning from phonology during sentence processing.

Abstract: The current study investigated whether shared phonology across languages activates cross-language meaning when reading in context. Eighty-five bilinguals read English sentences while their eye movements were tracked. Critical sentences contained English members of English-French interlingual homophone pairs (e.g., mow; French homophone mate mot means "word") or they contained spelling control words (e.g., mop). Only the meaning of the unseen French homophone mate fit the context (e.g., Hannah wrote another mow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This finding suggests that even when the reading context is highly constrained in one language, readers would still be able to activate phonology across languages. However, the shared phonology between English and Chinese interfered with rather than facilitated the activation of meaning in processing English sentences, inconsistent with the facilitation effect observed in the critical words in English-French bilinguals (Friesen, Ward, et al, 2020;Friesen, Whitford, et al, 2020). Notably, we used cross-script languages Chinese and English while Friesen, Whitford, et al (2020) used same-script languages English and French.…”
Section: Phonological Activation Of Words In a Sentence Contextmentioning
confidence: 72%
See 2 more Smart Citations
“…This finding suggests that even when the reading context is highly constrained in one language, readers would still be able to activate phonology across languages. However, the shared phonology between English and Chinese interfered with rather than facilitated the activation of meaning in processing English sentences, inconsistent with the facilitation effect observed in the critical words in English-French bilinguals (Friesen, Ward, et al, 2020;Friesen, Whitford, et al, 2020). Notably, we used cross-script languages Chinese and English while Friesen, Whitford, et al (2020) used same-script languages English and French.…”
Section: Phonological Activation Of Words In a Sentence Contextmentioning
confidence: 72%
“…To examine whether participants read sentences carefully, participants were asked to answer a comprehension question in 64 (78.05%) of the sentences, where half should be answered with “yes,” and the other half with “no.” For example, after the sentence “Abby experienced tone for a long time after she had back surgery,” the question was “Did Abby have a surgery on her back?” Note that among our comprehension questions, 18 out of 64 (28.13%) targeted the part of the sentence that included the homophone error or control error words, and 46 out of 64 (71.88%) did not. The purpose of including more comprehension questions that did not target the part of the sentences containing the homophone error or control error words is to ensure that our participants could answer the questions regardless of the error words (see also Friesen, Ward, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye-tracking studies with French-English bilinguals offer additional support for early activation of words in the non-target (inactive) language during reading (Friesen et al, 2020a(Friesen et al, , 2020bFriesen & Jared, 2012). Using a French-English homophone error paradigm, Friesen et al (2020a) found that readers were sensitive to phonological similarity across languages (i.e., the homophones "mow" and "mot"), with homophone effects observed in early eye-tracking measures. Similarly, Friesen et al (2020b) demonstrated that readers exhibited shorter fixations on homophone errors as opposed to spelling control errors, particularly on high-frequency words.…”
Section: Introductionmentioning
confidence: 97%
“…Prior eye-tracking studies of sentence reading (e.g., Titone et al, 2011;Pivneva et al, 2014;Whitford and Titone, 2015;Friesen et al, 2020) and paragraph reading (e.g., Whitford and Titone, 2012;Whitford and Titone, 2015) have highlighted the influence of current L2 exposure on lexical access and reading fluency. Many studies reported bidirectional L1-L2 influences that are modulated by individual differences in current L2 exposure, although these studies were not focused on syntactic processing per se.…”
Section: Introductionmentioning
confidence: 99%